Q-switched pulse operation in erbium-doped fiber laser subject to CdS nanoparticles-based saturable absorber deposit directly on the fiber ferrule - Asghar, Haroon; Ahmed, Rizwan; Sohail, Muhammad; Umar, Zeshan A.; Baig, M. Aslam (Optical materials, 2022)
In this work, we demonstrate the performance of a Q-switched erbium-doped fiber laser (EDFL) using a cadmium-sulfide (CdS) nanoparticle-based saturable absorber (SA). The CdS nanoparticles were deposited on the fiber ferrule using the adhesion effect of the index matching gel. By incorporating the CdS nanoparticles on the fiber ferrule, a self-starting and stable Q-switched operation started under 11.2 mW pump power. As the pump power of EDFL based on the CdS-SA was increased from 11.2 to 297 mW, the emission wavelength varied from 1564.16 nm to 1568.83 nm, the pulse repetition rates, and pulse duration ranged from 20 to 90.25 kHz and 15.2 to 3.5 μs, respectively. The maximum average output power, pulse energy, and peak power were measured as 2.55 mW, 28.26 nJ, and 8.07 mW, respectively at a maximum available pump power of 297 mW. Furthermore, the stability of EDFL based on CdS nanoparticles based SA was further investigated. This study suggests that CdS nanoparticles-based SA offers an easy fabrication and integration of SA inside the laser cavity to generate a pulse operation in fiber lasers. •Deposition of cadmium-sulfide (CdS) nanoparticles on a fiber ferrule to act as a saturable-absorber (SA).•The Q-switched pulse operation of EDFL based on CdS-SA emits at 1568.83 nm wavelength, operates at 90.25 kHz and yield minimum pulse width of 3.5 μs at maximum available pump power of 297 mW.•Investigation of long-term stability with no significant shift in center wavelength and pulse duration.